A re-examination of doubtful New Zealand tick records: lost species, misidentifications or contamination?. Issue 2 (2nd July 2016) - Heath, A.C.G.; Palma, R.L.
ABSTRACT: In the early twentieth century, three species of ticks – Haemaphysalis leachii, Hyalomma aegyptium and Ixodes ricinus – were originally thought to be part of the New Zealand fauna. In the absence of any firm evidence for their continued existence in this country, and without any satisfactory explanation for their original appearance, they were deleted from faunal lists about 60 years later. After consulting all relevant literature, we have dismissed the original suggestion that both the ticks Ha. leachii and Hy. aegyptium – originally taken from a museum specimen of the extinct huia, Heteralocha acutirostris – were introduced along with the Indian myna, Acridotheres tristis . Instead we find that there was a greater chance that their presence was the result of contamination, possibly through the collecting efforts and extensive travel of Walter L. Buller, a nineteenth-century naturalist and ornithologist. Further, although Hy. aegyptium was correctly identified, the other huia tick is actually Haemaphysalis ( Rhipistoma ) indica, not Ha. leachii sensu stricto . The taxonomic history of Ha. leachii (but not the other two species) has been convoluted and the spelling of the species epithet has frequently been contradictory. We briefly examine this history and clarify the correct spelling of that species name. We conclude that the supposed presence of I. ricinus was due to misidentification, possibly being confused with the cattle tick, Haemaphysalis longicornis, or the kiwi tick, Ixodes anatis .